2020
DOI: 10.1002/celc.202000242
|View full text |Cite
|
Sign up to set email alerts
|

On the Resistances of a Slurry Electrode Vanadium Redox Flow Battery

Abstract: We studied the half-cell performance of a slurry-based vanadium redox flow battery via the polarization and electrochemical impedance spectroscopy methods. First, the conductive static mixers are examined and lower ohmic and diffusion resistances are shown. Further analyses of the slurry electrodes for the catholyte (VO 2 + À VO 2 + ) and anolyte (V 3 + À V 2 + ) are presented for the graphite powder slurry containing up to 15.0 wt.% particle content. Overall, the anolyte persists as the more resistive half-ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…Induced dipoles created in each conducting particle by an external applied field generate a physical contribution to charge transfer, and also favor chemical charge transfer mechanism that result in an enhanced effective area. Thus, carbon enhances conductivity not only when part of solid electrode materials, but also when in suspension in the electrochemical cells [ 32 ].…”
Section: Comparison Of Nanostructured Iro X -Nanocarbon Hybrid Materials For Various Nanocarbon Particlesmentioning
confidence: 99%
“…Induced dipoles created in each conducting particle by an external applied field generate a physical contribution to charge transfer, and also favor chemical charge transfer mechanism that result in an enhanced effective area. Thus, carbon enhances conductivity not only when part of solid electrode materials, but also when in suspension in the electrochemical cells [ 32 ].…”
Section: Comparison Of Nanostructured Iro X -Nanocarbon Hybrid Materials For Various Nanocarbon Particlesmentioning
confidence: 99%
“…The slurry electrode or flow electrode is a dispersion of the electrolyte and electrode particles (and in some cases with conductive agents) to form a three-dimensional flowable electrochemically conductive network. Inspired by significant advantages of flowable active species with decoupled energy and power densities, large-scale energy storage units, such as redox flow batteries, have been developed. , However, low energy density from low ion solubility is a major drawback for redox flow batteries . On the other hand, semi-solid flow cells introduce the idea of replacing dissolved ions with solid conductive particulates to increase energy density, which can also be found in vanadium redox flow batteries , or zinc–nickel batteries; however, the cost of vanadium or other active materials is a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…Dennison et al investigated the electrochemical flow capacitor system and found that the geometry of the flow cell and slurry flow rate have substantial effects on the electrical conductivity of the slurry electrode . Percin et al studied fluid flow properties of vanadium redox flow batteries and pointed out that turbulent flow regimes offer better mixing and collision chances (between particles and current collectors and interparticle contacts) than laminar flow . Therefore, the particle contact time, collision frequency, mass loading, electrolyte resistance, size and shape of both particles and current collectors, and pore sizes and pore geometries of the particles are the key factors to regulate charge transfer. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The increasing amount of particles cause a low ionic conductivity due to blocked ionic pathways. In contrast, higher particle content improve the charge transfer from the current collectors to the particles, because more particles enables more electronic conductivity [35]. Polarization study is done by performing constant current charge and discharge on the battery and the voltage response of the system is recorded after it reaches to a stable state.…”
Section: Cell Designmentioning
confidence: 99%